Disraeli and Peacock - Freya Johnston (Cahiers Victoriens et Edouardiens)
When Benjamin Disraeli met Thomas Love Peacock in 1848, he greeted him—to Peacock’s apparent surprise—as his ‘master’. Why should Disraeli have considered the prose satirist who was Shelley’s contemporary to be the leading influence on his early literary career? In seeking to answer this question my article draws on Isaac D’Israeli’s Flim-Flams! Or the Life and Errors of My Uncle, and the Amours of My Aunt (1805), a work never mentioned by his son, as well as on other points of historical, biographical, and stylistic connection between Peacock’s novels and the so-called ‘Silver Fork’ or ‘Dandy’ School to which Vivian Grey (1826‒27) belongs.